The Dog Owner's Handbook - Meadows, Graham; Flint, Elsa. (London : Greenwich Editions, 2005)
This text will enable dog owners to understand and control their dog's behaviour, protect their pet from hazards and illness, monitor its health, deal with emergencies, cope with its aging and make better use of the veterinary clinic.
Originally published: London: New Holland, 2001.
Includes index.
Keywords: Dogs; Pets